2014
DOI: 10.4103/0973-1296.127346
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of nine major active components in traditional Chinese prescription Mahuang decoction and the influence of herbal compatibility on their contents

Abstract: Background:Mahuang decoction (MHD), a famous classic traditional Chinese formula, has been extensively applied for treating cold, influenza, asthma, acute bronchitis, and other pulmonary diseases. However, the interaction among four drugs of MHD has not been clearly deciphered from the aspect of molecular composition.Objective:To assess the quality of MHD and explore the interplay among different prescription drugs.Materials and Methods:A reversed-phase high performance liquid chromatography (RP-HPLC) coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Modern pharmacological studies indicate that the Ephedra herb has anti-inflammatory (Hiroshi et al, 1980), sudorific (Liu et al, 2006), antipyretic (Nagai et al, 2014), analgesic and anti-influenza effects (Mantani et al, 1999). Although Ephedra herb contains other constituents, such as phenolics, volatile oil and tannins, most pharmacological activities of the plant have been attributed to Ephedrine alkaloids (He et al, 2014; Li, 2015). Therefore, in the present study, based on the significant antiviral effects of LMEP, LEP and DPEP in vitro , we chose to conduct further mechanism studies on these three Ephedrine alkaloids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern pharmacological studies indicate that the Ephedra herb has anti-inflammatory (Hiroshi et al, 1980), sudorific (Liu et al, 2006), antipyretic (Nagai et al, 2014), analgesic and anti-influenza effects (Mantani et al, 1999). Although Ephedra herb contains other constituents, such as phenolics, volatile oil and tannins, most pharmacological activities of the plant have been attributed to Ephedrine alkaloids (He et al, 2014; Li, 2015). Therefore, in the present study, based on the significant antiviral effects of LMEP, LEP and DPEP in vitro , we chose to conduct further mechanism studies on these three Ephedrine alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Although MHT has long been considered as a typical formula for cold, its chemical ingredients that exert the main efficacy are still obscure. Modern pharmacological studies show that the nine components, including L-ephedrine (LEP), D-pseudoephedrine (DPEP), L-methylephedrin (LMEP), cinnamic alcohol (CAO), cinnamic acid (CMA), cinnamic aldehyde (CMD), amygdalin (AMY), liquiritin (LIQ) and glycyrrhizic acid (GA), are major bioactive ingredients by which MHT produces efficacy, and they are relatively high in content (He et al, 2014; Yu et al, 2017; Wei et al, 2018a) (their chemical structures are shown in Figure 1 ). Therefore, in the present study, the influenza virus-infected MDCK cells were utilized as carriers to evaluate the in vitro antiviral effects of nine predominant ingredients, and the potential mechanisms were principally elucidated both in vitro and in vivo , with the aim to screen the antiviral components of MHT, as well as provide a certain basis for further research and theoretical references for the clinical rational use of MHT.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile phase consisted of 0.05% formic acid-0.05% triethylamine aqueous solution (A) and acetonitrile (B) with the gradient elution program as follows: 0–15 min, 8–10% B; 15–20 min, 10% B; 20–50 min, 10–27% B; 50–55 min, 27–38% B; 55–60 min, 38% B; 60–65 min, 38–8% B; 65–75 min, 8% B. The detection wavelengths were 210, 252, 278 and 291 nm ( He et al, 2014 ). The injection volume was 10 μ l. The chromatogram of MHD was presented in Supplementary Figure S1 .…”
Section: Methodsmentioning
confidence: 99%